Beating Adolescent Self-Harm (BASH): a randomised controlled trial comparing usual care versus usual care plus a smartphone self-harm prevention app (BlueIce) in young adolescents aged 12–17 who self-harm: study protocol - Gordon Taylor; P Stallard; Antonieta Medina-Lara; Shelley Rhodes; Isobel Greenhalgh; Jessica Tingley (BMJ Open, 2021)
Introduction A mobile app, BlueIce, was codesigned with young people with a history of self-harm to provide them with more accessible and available evidence-based support at times of distress. A preliminary evaluation found that BlueIce was acceptable, safe and used by young people and helped to reduce self-harm. The present study is designed to assess the effectiveness and cost-effectiveness of adding BlueIce to usual Child and Adolescent Mental Health Service (CAMHS).Methods and analysis This study is a single-blind, randomised controlled trial comparing usual CAMHS care with usual care plus BlueIce. A total of 138 adolescents aged 12–17 with current or a history of self-harm will be recruited through the Oxford Health National Health Service (NHS) Foundation Trust via their CAMHS clinician. The primary outcome is self-harm at 12 weeks assessed using the Risk Taking and Self-Harm Inventory for Adolescents. Secondary outcomes include mood, anxiety, hopelessness, general behaviour, sleep and impact on everyday life at 12 weeks and 6 months. Health-related quality of life and healthcare resource utilisation data will be collected at baseline, 12 weeks and 6 months. Postuse interviews at 12 weeks will determine the acceptability, safety and usability of BlueIce.Ethics and dissemination The study was approved by the NHS South Central—Oxford B NHS Research Ethics Committee (19/SC/0212) and by the Health Research Authority (HRA) and Health and Care Research Wales. Findings will be disseminated in peer review open-access journals and at academic conferences.Trial registration number ISRCTN10541045.